Favorable Cardiovascular Health, Compression of Morbidity, and Healthcare Costs: Forty-Year Follow-Up of the CHA Study (Chicago Heart Association Detection Project in Industry). Issue 18 (2nd May 2017) - Allen, Norrina B.; Zhao, Lihui; Liu, Lei; Daviglus, Martha; Liu, Kiang; Fries, James; Shih, Ya-Chen Tina; Garside, Daniel; Vu, Thanh-Huyen; Stamler, Jeremiah; Lloyd-Jones, Donald M.
Abstract : Background: We examined the association of cardiovascular health at younger ages with the proportion of life lived free of morbidity, the cumulative burden of morbidity, and average healthcare costs at older ages. Methods: The CHA study (Chicago Heart Association Detection Project in Industry) is a longitudinal cohort of employed men and women 18 to 74 years of age at baseline examination in 1967 to 1973. Baseline measurements included blood pressure, cholesterol, diabetes mellitus, body mass index, and smoking. Individuals were classified into 1 of 4 strata of cardiovascular health: favorable levels of all factors, 0 factors high but ≥1 elevated risk factors, 1 high risk factor, and ≥2 high risk factors. Linked Medicare and National Death Index data from 1984 to 2010 were used to determine morbidity in older age. An individual's all-cause morbidity score and cardiovascular morbidity score were calculated from International Classification of Disease, Ninth Revision codes for each year of follow-up. Results: We included 25 804 participants who became ≥65 years of age by 2010, representing 65% of all original CHA participants (43% female; 90% white; mean age, 44 years at baseline); 6% had favorable levels of all factors, 19% had ≥1 risk factors at elevated levels, 40% had 1 high risk factor, and 35% had ≥2 high risk factors. Favorable cardiovascular health at younger ages extended survival by almost 4 years and postponed the onset of all-cause and cardiovascular morbidity by 4.5 and 7 years, respectively, resulting in compression of morbidity in both absolute and relative terms. This translated to lower cumulative and annual healthcare costs for those in favorable cardiovascular health ( P <0.001) during Medicare eligibility. Conclusions: Individuals in favorable cardiovascular health in early middle age live a longer, healthier life free of all types of morbidity. These findings provide strong support for prevention efforts earlier in life aimed at preserving cardiovascular health and reducing the burden of disease in older ages. Abstract : Supplemental Digital Content is available in the text.